Management Development of Problem-Based Learning - Ikhfan Haris (AL-ISHLAH: Jurnal Pendidikan, 2021)
Problem-based learning has been used in high school classrooms for a long time. Despite all the theory and practical recommendations on the usefulness of problem-based learning, empirical research reveals that it primarily impacts problem-solving. Critical thinking problems and talents, but not necessarily knowledge. Various theoretical techniques, which are addressed in this work, can assist problem-based learning. After that, a detailed assessment of the empirical literature on problem-based learning is offered, focusing on its use in Informatics Technology Education classrooms. This study utilises the literature study approach to complete this study, which entails acquiring and analysing data from various sources. Existing theoretical concepts, such as problem-based learning, do not link theory with relevant research as well as new pedagogical theories. In problem-based learning, objectives and learning outcomes take precedence over time and resources. According to this study, problem-based learning will increase student learning assessment in the future.